Analysis of the Role of Political Parties in Political Education in View of the Applicable Political System in Indonesia - Ariyanti Luhur Tri Setyarini; AS Martadani Noor; Vicki Dwi Purnomo (Formosa Journal of Applied Sciences, 2023)
This research Has political education been carried out for citizens? What is the role of political parties in political education in Indonesia? As for the purpose of study This is For know about function party political in political education as an effort to increase political participation. The method used in this study is library research ( library research ), namely studying, analyzing and formulate problem through books or document. From results study concluded education politics is to provide an understanding to citizens about the rights and his obligations in life nation and patriotic.